Culture Shock sebagai Mediator antara Kepribadian Reformer terhadap Sojourner Adjustment - Ujam Jaenudin; Dadang Sahroni; Zulmi Ramdani (Psympathic : Jurnal Ilmiah Psikologi, 2020)
This study was conducted to determine the role of culture shock as a mediator between personality reformers and sojourner adjustment. The quantitative research design was used in this study of Muslim students from the Pattani province in Southern Thailand who were studying in Bandung. Respondents involved in this study were 225 people selected using saturated sampling techniques. Data were collected by distributing questionnaires containing 3 measuring tools that have been modified by the author including reformer personality scale, sojourner adjustment scale, and culture shock scale. Data analysis using SEM (Structural Equation Modeling). This study concludes that the theoretical model of the role of reformer personality on sojourner adjustment through cultural shock mediators is fit with empirical data. Structural analysis shows that cultural shock is a significant mediator variable on the influence of reformer personality on sojourner adjustment.